User Experience Design of History Game - Wong, Seng Yue; Ghavifekr, Simin (IGI Global, 2018)
User experience (UX) and user interface design of an educational game are important in enhancing and sustaining the utilisation of Game Based Learning (GBL) in learning history. Thus, this article provides a detailed literature review on history learning problems, as well as previous studies on user experience in game design. Future studies on educational history games will benefit from this systematic review and analysis of current educational history games, as this article examines in detail which game features are the most effective in promoting engagement and supporting the process of learning Malaysian history. The results have revealed that mobile game applications with historical content can indeed be a meaningful way to create gaming experience, learning experience, adaptivity and usability, which can facilitate history learning through UX of playing history mobile games. The correlation results of these four dimensions have indicated four positive and significant relationships.